RISIKO PEMBIAYAAN MURABAHAH PADA BANK SYARIAH - Myrna Dwi Tantia; Lidya Asterina; Muhammad Arif (Jurnal At-Tabayyun, 2020)
Islamic banking practices have gained significant attention in the global financial industry. One of the most commonly used financing modes in Islamic banking is Murabahah. This study aims to analyze the risks associated with Murabahah financing in Islamic banks. The research delves into the various risk factors that Islamic banks face when engaging in Murabahah transactions and the strategies employed to mitigate these risks. The findings shed light on the importance of risk management in Islamic banking and its implications for the industry's growth and stability.